2014
DOI: 10.1002/nau.22581
|View full text |Cite
|
Sign up to set email alerts
|

Liquid paraffin is superior to 2% lidocaine gel in reducing urethral pain during urodynamic study in men: A pilot study

Abstract: Liquid paraffin is more efficient than 2% lidocaine gel in reducing urethral pain during Urodynamic study in men. Pain scores were specifically better during the instillation of the lubricant and during the delivery of the urethral catheter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…According to previous randomized control studies [5,6], a sample size of 100 (50 per group) was needed, assuming a 5% statistical significance level and 95% power to detect a minimum difference of 10 mm in the mean procedural pain score between the 2 groups with a SD of 1 point. For normal and non-normal distributions, statistical significance was determined by t test and the Mann-Whitney U test, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…According to previous randomized control studies [5,6], a sample size of 100 (50 per group) was needed, assuming a 5% statistical significance level and 95% power to detect a minimum difference of 10 mm in the mean procedural pain score between the 2 groups with a SD of 1 point. For normal and non-normal distributions, statistical significance was determined by t test and the Mann-Whitney U test, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Several approaches relieve anxiety, pain, and distress such as reading an information leaflet, lubricant, and local anesthetic during catheterization. [14][15][16][17] Other effective and nonpharmacologic alternative treatment modalities also can be considered.…”
mentioning
confidence: 99%
“…Ho tested 2% lidocaine gel against plain aqueous gel in a placebo-controlled trial of 100 male patients undergoing flexible cystoscopy, and concluded that lidocaine gel causes urethral pain rather than preventing it, and now Stav et al suggest that lidocaine gel is no better than plain lubricants. 1 Is intraurethral topical anesthesia not necessary or it is not effective enough? It is clear that the superficial layer of the uroepithelium is not tolerant against friction and is sensitive to various injuries, thus intraurethral instrumentation is a potentially painful procedure.…”
Section: Dear Editor In Chiefmentioning
confidence: 99%
“…There are also controversial issues regarding the need for local anesthesia during urethral instrumentation. Birch tested 2% lidocaine against plain lubricating gel for cystoscopy in a placebo‐controlled trial of 138 patients, and concluded that the topical anesthetic is no more effective than “good lubrication.” Ho tested 2% lidocaine gel against plain aqueous gel in a placebo‐controlled trial of 100 male patients undergoing flexible cystoscopy, and concluded that lidocaine gel causes urethral pain rather than preventing it, and now Stav et al suggest that lidocaine gel is no better than plain lubricants …”
mentioning
confidence: 99%
See 1 more Smart Citation